VISIT BY UoB PRO VICE-CHANCELLOR OPENS POSSIBILITIES FOR COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
NIBONG TEBAL, 24 February 2016 – A visit by the Pro ViceChancellor, Professor Collin Grant from the University of Bath (UoB), United Kingdom to the Universiti Sains Malaysia (USM) Engineering Campus recently has presented various opportunities for academic and research cooperation especially in the field of engineering.